Field Corn Production Guide - David Wright; Jim Marois; Jim Rich; Richard Sprenkel (EDIS)
Field corn is important in Florida for both grain and silage. Production has declined over the past two decades because of limited opportunities for profit, increased financial risks with less insurance coverage as compared to cotton and peanut, reduction in infrastructure for handling, and higher production costs. This is document SS-AGR-85, a publication of the Department of Agronomy, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: January 2004.